A Tragic Tory Leader and His Diaries. - Lexden, Alistair (Parliamentary History, 2018)
Sir Stafford Northcote, a tory with many liberal instincts, was leader of the Conservative Party in the Commons from 1876 to 1885 (outranking the leader in the Lords after 1881). Subjected to much harsh criticism during this period, his significant achievements over his long political career as a whole have been largely forgotten. His diaries contain a great deal of information about his activities in, and beyond, politics. Most of them exist today only in typescript copies. By a set of curious chances, four of the original diaries came into the possession of a lawyers' clerk. In 2017, they were added to Northcote's surviving papers in the British Library. All four relate to travel, mainly on important public business outside Europe. The final section of this note provides an indication of the interest and significance of these diaries.